A general and facile strategy for precisely controlling the crystal size of monodispersed metal–organic frameworks via separating the nucleation and growth. Issue 6 (13th December 2017) - Lan, Xiaocheng; Huang, Ning; Wang, Jinfu; Wang, Tiefeng
Abstract : Nucleation and growth were separated to precisely control the crystal size of MOFs. Abstract : A novel and facile strategy was proposed for precisely controlling the crystal size of ZIF-8, ZnCo bimetallic ZIFs and also NPs@ZIF-8 by separating the nucleation and growth. The fundamentals of crystallization of this strategy were elaborately investigated, and the size effect on the internal diffusion was explored for a series of Pt@ZIF-8 catalysts.